Etika Dan Budaya Politik “Konsep Sistem Politik Di Indonesia" - Hasanah, Uswatun; Kirani, Chintia; Gabylia, Elina Mitha; Adawiyah, Robiatul (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
Politics is basically a phenomenon that is closely related to humans, who by nature always live in society. Therefore, politics will always manifest itself in the framework of the process of human development. With the above connection, humans are the main core of political reality, whatever is captured or politically analyzed cannot simply leave humans. This shows that the essence of politics is human behavior, whether in the form of activities or attitudes aimed at influencing or maintaining the order of a society by using force. The constitutional exercise of power includes the distribution of political power which includes issues: sources of political power, legitimacy processes, highest authority holders, administration of power, functions of power/light tasks and easily accessible political goals.